Samotnik w Międzyludzkim, czyli o życiu i twórczości Emila Ciorana - Rososińska-Kozub, Natalia (Filozofia Chrześcijańska, 2015)
This essay constitutes an attempt of showing the dialectics of the phenomenons of solitude and community on the example of Romanian writer and philosopher, Emil Cioran’s works and life. The aim of this paper is to present the combination of Cioran’s writings and his private life in comparison with the game in which solitude and community plays the main roles. The complete profile of Cioran greatly references to a philosophical subdiscipline, monoseology which treats on the phenomenon of solitude with its all complexity. The writings of Emil Cioran is a mutual interweaving of loner’s striving for any community.